Smart Power : Between Diplomacy and War - Whiton, Christian (Book collections on Project MUSE., 2013)
From China's cyber war on America to Islamist victories across the Middle East to the lengthening shadow cast by Iran, the Washington establishment has failed to neutralize foreign threats that are becoming more dangerous. No one on the political left or right has articulated a realistic defense strategy to meet these new challenges of the twenty-first century. Smart Power -written by a prolific writer and TV commentator who saw firsthand the successes and failures of statecraft in the George W. Bush administration-offers new solutions to the threats America faces today, including radical refo.